2018
DOI: 10.1016/j.jvs.2018.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume as a Predictor for Restenosis After Carotid Angioplasty and Stenting

Abstract: that neurologists billed more for interpreting the EEG the day after the operation while drinking coffee than I did for doing the surgery (I cannot confirm or deny this claim, but the thought of it annoys me). The reader needs to pay close attention to any publication reporting SP thresholds and whether the authors measure mean or peak systolic pressures. The authors in the current paper made the mistake of not mentioning if threshold criteria reported in other papers were one or the other and lumped the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…[79][80][81] Choi et al 82 demonstrated that a combination of high NLR and high MPV independently predicted the risk of major adverse cardiovascular events, including cardiac death, nonfatal myocardial infarction, and stent thrombosis after PCI. Dai et al 83 evaluated the MPV as a predictor of carotid angioplasty and stenting restenosis, suggesting that patients with high preprocedural MPV may benefit from intensified antiplatelet therapy. In the multivariate regression analysis, baseline MPV >10.1 fL had a hazard ratio: 3.20, 95% CI: 1.28 to 8.03.…”
Section: Mean Platelet Volumementioning
confidence: 99%
“…[79][80][81] Choi et al 82 demonstrated that a combination of high NLR and high MPV independently predicted the risk of major adverse cardiovascular events, including cardiac death, nonfatal myocardial infarction, and stent thrombosis after PCI. Dai et al 83 evaluated the MPV as a predictor of carotid angioplasty and stenting restenosis, suggesting that patients with high preprocedural MPV may benefit from intensified antiplatelet therapy. In the multivariate regression analysis, baseline MPV >10.1 fL had a hazard ratio: 3.20, 95% CI: 1.28 to 8.03.…”
Section: Mean Platelet Volumementioning
confidence: 99%
“…Therefore, MPV value has been extensively investigated in cardiovascular diseases. The effect of MPV on restenosis after carotid artery stenting was investigated by Dai et al [16]. In this study, patients were followed for 12.1 (16.1) months and high MPV values before the procedure were found to be associated with restenosis.…”
Section: Discussionmentioning
confidence: 91%
“…Another study reported that CRP levels two days after the index carotid artery intervention was associated with ISR during six months period following CAS (23). In addition to the role of elevated CRP levels, preprocedural NLR, mean platelet volume, and the neutrophil and albumin ratio was found to be associated with the occurrence of ISR following CAS (24)(25)(26). In this study, we also found that a higher ratio of CAR, a new inflammatorybased index, is a strong predictor of ISR development after CAS.…”
Section: Discussionmentioning
confidence: 99%